TERRA recruitment of polycomb to telomeres is essential for histone trymethylation marks at telomeric heterochromatin - Juan J. Montero (Nature Portfolio, 2018)
Long non-coding RNA TERRAs are essential for telomere protection and telomere length maintenance. Here the authors report a role for TERRAs in telomeric heterochromatin formation by recruiting Polycomb Repressive Complex 2 to telomeres.